Media-Based Growth Mindset Intervention Model for Student Thesis Completion - Zakariyya, Farhan; Lestari, Selfiyani; Hidayat, Ghinaya Ummul Mukminin; Larasati, Anissah; Musthofa, Muhammad Ariez; Kosasih, Engkos (Jurnal Psikologi, 2026)
Background: Growth mindset is a condition that has been proven to have a high role in producing good psychological conditions and determining student success in learning. However, growth mindset interventions generally take a long time to implement. Therefore, simpler growth mindset intervention designs are currently at the centre of researchers' attention.Purpose: This study aims to examine the effectiveness of media-based growth mindset intervention on students' final project completion.Method: The method used was a between-subjects experiment with a randomized pretest-posttest experimental design. There were 25 participants involved in experimental group 1 (video media), and 30 participants involved in experimental group 2 (infographics). The measuring instrument used were the growth mindset scale and study success measured through the achievement indicators at the stage of thesis completion. Data analysis was conducted using the t-test.Findings: The results of the analysis showed a significant increase in scores in all three pairs of variables. The video intervention showed a significant difference between pre and post scores, as did the infographic intervention. Meanwhile, the thesis achievement variable measured three months after the intervention showed a much stronger and significant improvement. During the three months of progress, participants completed their thesis although they were not making a research title or only reached chapter 3 at the beginning of the intervention.Implication: This intervention can be used for universities to overcome students who experience difficulties or encourage students to graduate on time.